Livro didático de língua portuguesa: implicações sobre o processo de avaliação e o ensino - Almeida, Marcela Bandeira de Mello (2014)
In searching to deepen and widen the theoretical and methodological perspective studies involving the portuguese student’s book used in the evaluation and teaching process, we defend in this quantity and quality study, the necessity of analyzing in an interdisciplinary field which involves the teacher’s participation, who represents the mediator between the student and the student’s book. This research investigated the questions about evaluations of the portuguese student’s books in the early years of elementary teaching approved by the National School Book Program for 2013, 2014 and 2015 which were divided up into four segments: reading, writing, speech and grammar, taking into consideration the student’s book as the main tool in the evaluation and the teaching process of the portuguese language. The theory contemplates authors into the evaluation: Demo (2012), Esteban (2003), Depresbiteres (1991), on the teaching of the portuguese language: Antunes (2013), Soares (2004), Travaglia (2009) and in reference to the student’s book as the subject of research: Choppin (2004), Dell’Isolla (2008), Lajolo (2006), Batista (2001), among others. The subject of this research will show contributions in the following fields: Linguistics, applied linguistics and education, since we believe that the approach of the questions referred to the teaching and evaluation of the language requires from the researcher an interdisciplinary study. We showed a discussion about the evaluation concepts in the classes of the portuguese language, as well as concepts of teaching the language and the connection between concepts and teaching practices. This research also involved a brief discussion of questions about the formation of the teachers to cover the multiples ways about this subject. We also investigate about the evaluating and teaching concepts that were in the teacher’s manuals, which come with the student’s books. Taking into consideration how relevant the research about the evaluation and teaching of the Portuguese language, we would like to contribute to the educational and linguistic debates and to the review of the evaluation and teaching concepts. This study’s conclusion points to the majority of the questions proposed analyzing the collections such as writing and reading. Speech was explored very little by some authors and the ones about grammar were practically non-existent in the reading process. The learning concepts of evaluation were predominating formative, as there have been variations in terminology, since some authors denominated their proposal of evaluation basically as procedural or mediator. It also became clear that this research’s subjects were committed with a theoretical and methodological way of evaluation and teaching that emphasize the meaning of learning and that the use of student’s books as a teaching tool in the classroom should be used with other teaching resources that will broaden the teaching and learning possibilities in the school environment.